Manajemen Strategi dalam Mempercepat Pelaksanaan Proyek Konstruksi pada Pt XY di Makassar - Murbayani Murbayani (Universitas Islam Negeri Alauddin Makassar, 2015)
This study aims to determine the right strategy used by PT. XY to accelerate the implementation of construction projects in Makassar City. The population study is all parties concerned with PT. XY, consisting of the Department of Public Works, the company associates, Planning Consultant, Supervisor, and employees of PT. XY own. The research sample determined by purposive sampling that establishes a sample on the basis that the respondents to determine the condition of the implementation of construction projects undertaken by PT. XY. Analyzer used in this research is using SWOT analysis (Strength, Weakness, Opportunity and Threat). The using of this analysis is a combination of external factors (opportunities and threats) and internal factors (strengths and weaknesses). Based on the analysis, it is known that through the preparation of a SWOT diagram obtained that position PT. XY in an effort to expedite the completion of the construction project, located in quadrant I (first). This means that in an effort to accelerate the completion of construction projects, PT. XY has some internal factors such as the strength of openness in management, adequate manpower skills, commitment of human resources is high, the motivation of the project team, the availability of sufficient infrastructure and refresentatif, and opportunities such as regulation or regulations governing the operation of services construction, the method (CPM and PERT) that can be used to create a network of shorter, the monitoring and evaluation of the Department of Public Works, the existence of a third party who is willing to supply the material, and the presence of the Bank is willing to lend funds. Therefore we need a strategy that can harness the power of PT. XY to seize opportunities (Strenght Opportunity Strategy) or aggressive strategies, such as using CPM or PERT critical time in the planning and allocation of resources.